(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The study aimed to test the reflection of strategic planning in the supply chain represented by primary resources and transportation in some oil companies in Nineveh Governorate, as it expressed strategic planning (an independent variable) and the supply chain (a dependent variable) represented by its dimensions (raw materials, transportation), in an attempt to address Research problem: Do the supply chains in the surveyed organizations depend on what strategic planning reflects on them? To achieve this goal, hypotheses were formulated for the study that reflects the correlation between the variables of the study, and the impact of strategic planning on the supply chain. To test these hypotheses, the descriptive analytical approach was adopted. The questionnaire was used as a main tool in collecting data from the field under study (oil companies in Nineveh Governorate), as it was distributed to a sample of From (108) respondents from administrative and production leaders, and adopted the statistical software (spss-v26) in analyzing the data and reached several results, the most important of which are: the existence of a correlation between strategic planning, the supply chain represented by primary resources and transportation, and the existence of an impact of strategic planning in the supply chain represented by primary resources And the transfer, and in a way that led to the submission of recommendations and proposals that relied on officials and administrative leaders in the companies surveyed to set clear goals and disclose the main and subsidiary goals for them in a way that avoids misinterpretation of them in order to achieve them quickly and efficiently